Tribological evaluation of joint fluid and the development of a synthetic lubricant for use in hip joint simulators - Burger, N.D.L (Nicolaas Daniel Lombard) (University of Pretoria, 2013)
Dissertation (MEd (Mechanical Engineering))--University of Pretoria, 2006.